Promosi Rumah Ong Boen Tjiet Sebagai Warisan Budaya Tionghoa Di Kota Palembang - Ismi Oktari; Aji Windu Viatra; Yosef Yulius (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
The promotion of Rumah Ong Boen Tjiet as a Chinese cultural heritage site in the city of Palembang is driven by the declining public awareness, particularly among the younger generation, toward local cultural heritage due to the influence of globalization and the dominance of popular culture in digital media. Rumah Ong Boen Tjiet is a historical building that represents the acculturation between Chinese culture and local Palembang culture, as reflected in its architecture, ornaments, and historical values. However, the lack of effective promotional strategies, along with suboptimal environmental conditions and accessibility to the site, has resulted in limited public recognition. Therefore, a visual communication strategy is needed to introduce and enhance public awareness of the cultural and historical significance of this site. The objective of this design project is to develop a promotional identity that represents the historical and cultural values of Rumah Ong Boen Tjiet, while also formulating an effective promotional strategy that remains relevant in the context of modern media development. The method used in this project is the Design Thinking approach, which includes the stages of empathize, define, ideate, prototype, and test. Data collection techniques involve observation, interviews, documentation, and literature studies. The results of the project indicate that the use of visually based promotional media, such as promotional videos and other visual communication tools, can enhance the attractiveness of cultural information and expand the reach of publication, especially among younger audiences. Thus, this design is expected to support the preservation of Rumah Ong Boen Tjiet as part of cultural heritage and as a cultural tourism destination in the city of Palembang